Dermatitis Associated with the Intake of Defatted Rice Bran by Cattle in the Southern Region of the State of Rio Grande do Sul - Santos, Ederson dos; Barbosa, Antônio Amaral; da Fonseca, Rodrigo Fonseca; Rabassa, Viviane Rohrig; Schmitt, Eduardo; Correa, Marcio Nunes (Acta Scientiae Veterinariae, 2021)
Background: Dermatitis associated with defatted rice bran (DRB) seems to be an underdiagnosed disease in Brazilian confined herds, characterized by localized skin lesions that develop mainly on hind limbs, and can affect any animal category. In this context, the goal of the present study was to describe an outbreak of dermatitis associated with the consumption of defatted rice bran on a property in the State of Rio Grande do Sul, demonstrating the clinical, hematological and epidemiological characteristics of the animals, as well as alternatives for the definitive diagnosis. Cases: Clinical and epidemiological data were obtained by anamnesis with the technician responsible for the property. Aberdeen Angus and crossbred males, with 24 to 36 months of age, with an average of 413 kg, from a property in the interior of the state of Rio Grande do Sul were analyzed. From a batch of 45 cattle, from 24 to 36 months of age, 20 presented lesions on hind limbs 8-17 days after supplementation of a commercial feed containing defatted rice bran. To assist in the diagnosis, blood samples were drawn into vacuum tubes with 10% EDTA, for a complete blood count with the investigation of hemoparasites, and without anticoagulant, for liver function tests. In addition, lesion tissue samples were also collected for bacteriological, mycological and histopathological examination and the ration offered to the animals, for intradermal tests. There were no significant hematological and biochemical changes in animals that developed DRB dermatitis, except when they have an associated secondary infection. The fungal research was negative. The bacterial culture revealed a growth of Staphylococcus aureus, possibly due to secondary infection resulting from the lesions. In histopathological examination, lesions were characterized by areas of alopecia, thickening of the epidermis, forming dry, thick crusts, and some ulcerative and serosanguineous lesions. Histologically, lesions were characterized by marked hyperkeratosis, ulceration, and in the superficial dermis, intense inflammatory infiltrate of eosinophils and lymphocytes.Histologic changes, although not pathognomonic, are typically described in this disease. The intradermal test was performed to contribute to the diagnosis of the disease, where a significant increase in volume was found between measurements on animals that developed the disease. It is believed that the disease is produced due to a food hypersensitivity as a consequence of the high protein level in DRB. The results of the intradermal test indicate that the animals developed hypersensitivity and reaction to proteins, and further research is required to determine the protein fraction leading to hypersensitivity reactions. Discussion: In the present study, acute lesions in hind limbs in a significant number of animals of the same batch in a short period of time after supplementation with a diet containing defatted rice bran, enabled a clinical diagnosis suggestive of dermatitis associated with DRB consumption. Through epidemiological data, reactive intradermal test, associated with the findings of the histopathological exam, which showed characteristic lesions of the disease (alopecia, erythema, epidermis thickening, with the formation of thick crusts, usually on hind limbs in the region of the hoof coronary band, progressing to pastern and fetlock), it was possible to establish the clinical-pathological diagnosis of dermatitis associated with the consumption of defatted rice bran. Keywords: dermatitis, cattle, supplementation, defatted rice bran. Descritores: dermatite, bovinos, suplementação, farelo de arroz desengordurado. Título: Dermatite associada ao consumo de farelo de arroz desengorduradoem bovinos na região sul do Estado do Rio Grande do Sul.